Mediasi Penal Bagi Anak yang Berkonflik dengan Hukum - Herlita Herlita Eryke; Herlambang Herlambang (Universitas Bengkulu, 2020)
Juvenille against the law (ABH) in the Child Criminal Justice System (SPPA) must receive a special approach, special attention, special consideration, care, special services and special protection because ABH has limitations compared to adults. Based on the purpose of SPPA is the best interst for children. According to Law Number 11 Year 2012 the settlement of child cases must be based on Penal Mediation. Penal mediation focuses justice on the victim according to personal interests, but is still able to hold the offender responsible for the crime he committed. The justice offered is a remedy for all parties involved. Law enforcement officials, juvenilles, families, victims and the community can agree to divert the case so that it is not brought to the criminal justice system. The study aims to describe the implementation of penal mediation at every level of the juvenile justice system in the Bengkulu District Court. research using socio-legal research research methods. By collecting data and information and the facts of the symptoms in the field, both through observation, interviews and documentation. Data collected in the form of primary data and secondary data, selected purposively according to the characteristics of the data. Data analysis was performed descriptively with inductive and deductive approaches. The results of the study found that the implementation of penal mediation in every level of the criminal justice system has been carried out in accordance with the SPPA Law but there are no standard implementation standards of the mediation process of penalties against children in conflict with the law, the implementation has not been effective. The most common penal mediation is at the level of the police investigator because it is the main gate of the juvenile justice system